A twofold reduction in the incidence of acute ankle sprains in volleyball after the introduction of an injury prevention program: a prospective cohort study - Bahr, R.; Lian, O.; Bahr, I. A. (Scandinavian Journal of Medicine & Science in Sports, 1997)
The purpose of this study was to examine the effects of an injury prevention program, consisting mainly of an injury awareness session, technical training (with emphasis on proper take-off and landing technique for blocking and attacking) and a balance board training program, for players with recurrent sprains. Baseline data were collected during the 1992-93 season and the program was introduced during the 1993-94 season. The 1994-95 season was used to evaluate the effects of the prevention program. The coaches and players in the top two division of the Norwegian Volleyball Federation kept monthly records of exposure time and acute injuries (causing a player to miss at least one playing day). The total exposure time was 149968 h, 132757 h of training and 17211 h of match play during the three seasons. The incidence of ankle injuries was reduced from 0.9 +/- 0.1 per 1000 player hours during the 1992-93 season (48 injuries) to 0.7 +/- 0.1 during the 1993-94 season (38 injuries; NS vs. 1992-93) and to 0.5 +/- 0.1 during the 1994-95 season (24 injuries, P < 0.01 vs. 1992-93). Scand J Med Sci Sports 1997 Jun;7(3):172-7